Hydrodynamic and Thermophoretic Effects on the Supramolecular Chirality of Pyrene‐Derived Nanosheets. Issue 26 (26th May 2015) - Micali, Norberto; Vybornyi, Mykhailo; Mineo , Placido; Khorev, Oleg; Häner, Robert; Villari, Valentina
Abstract Chiroptical properties of two‐dimensional (2D) supramolecular assemblies (nanosheets) of achiral, charged pyrene trimers (Py3) are rendered chiral by asymmetric physical perturbations. Chiral stimuli in a cuvette can originate either from controlled temperature gradients or by very gentle stirring. The chiroptical activity strongly depends on the degree of supramolecular order of the nanosheets, which is easily controlled by the method of preparation. The high degree of structural order ensures strong cooperative effects within the aggregates, rendering them more susceptible to external stimuli. The samples prepared by using slow thermal annealing protocols are both CD and LD active (in stagnant and stirred solutions), whereas for isothermally aged samples chiroptical activity was in all cases undetectable. In the case of temperature gradients, the optical activity of 2D assemblies could be recorded for a stagnant solution due to migration of the aggregates from the hottest to the coldest regions of the system. However, a considerably stronger exciton coupling, coinciding with the J‐band of the interacting pyrenes, is developed upon subtle vortexing (0.5 Hz, 30 rpm) of the aqueous solution of the nanosheets. The sign of the exciton coupling is inverted upon switching between clockwise and counter‐clockwise rotation. The supramolecular chirality is evidenced by the appearance of CD activity. To exclude artefacts from proper CD spectra, the contribution from LD to the observed CD was determined. The data suggest that the aggregates experience asymmetrical deformation and alignment effects because of the presence of chiral flows.